If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 21 = 3t Solving 21 = 3t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-3t' to each side of the equation. 21 + -3t = 3t + -3t Combine like terms: 3t + -3t = 0 21 + -3t = 0 Add '-21' to each side of the equation. 21 + -21 + -3t = 0 + -21 Combine like terms: 21 + -21 = 0 0 + -3t = 0 + -21 -3t = 0 + -21 Combine like terms: 0 + -21 = -21 -3t = -21 Divide each side by '-3'. t = 7 Simplifying t = 7
| 3ax-2=5ax-1 | | -3d+5+d15= | | f(x)=6xln(2x)-6x | | 11=-5g-2 | | (3x-1)(10x-3)=0 | | 3x+3(6x-12)=132 | | 3r-4rs+2s= | | 0.07=56 | | 72=9g | | 2X-21+3X-34=180 | | -4(5x+2)+3(x-3)= | | 2w-3(3w+5)=3w+5 | | -8x-5y=15 | | 35-19=3(x-3) | | ?(2x-4)+5=-?(x+1) | | 3x^3+13x^2-16=0 | | 48x^2-16x-20=0 | | -138-6(6b-7)= | | 2n-1=-11 | | 4x+8y=52 | | 3n-8=-20 | | 4x-10=12+4(x+8) | | 2-c=29 | | ?(2x-4)=-?(x+1) | | 4t-1=5(t+5) | | 3x=7x+20 | | 5(6+3r)+7127= | | 13mn-5nm+2mn= | | 6+5ln(2x-1)=21 | | 2x+14=8-3y | | x^2-15x+(56.25)=8 | | 1.6=2y+7.8 |